ChemInform Abstract: LiBi3S5 — A Lithium Bismuth Sulfide with Strong Cation Disorder. Issue 27 (16th June 2016) - Nakhal, Suliman; Wiedemann, Dennis; Stanje, Bernhard; Dolotko, Oleksandr; Wilkening, Martin; Lerch, Martin
Abstract: Phase‐pure LiBi3 S5 powder is prepared by solid state reaction of equimolar amounts of LiBiS2 and Bi2 S3 in H2 S (Al2 O3 crucible, 600 °C, 4 h).